A modified efficient method for dental pulp stem cell isolation - Maryam Raoof; Mohammad Mehdi Yaghoobi; Ali Derakhshani; Ali Mohammadi Kamal-abadi; Behnam Ebrahimi; Mehdi Abbasnejad; Noushin Shokouhinejad (Wolters Kluwer Medknow Publications, 2014)
Background: Dental pulp stem cells can be used in regenerative endodontic therapy. The aim of this study was to introduce an efficient method for dental pulp stem cells isolation. Materials and Methods: In this in-vitro study, 60 extracted human third molars were split and pulp tissue was extracted. Dental pulp stem cells were isolated by the following three different methods: (1) digestion of pulp by collagenase/dispase enzyme and culture of the released cells; (2) outgrowth of the cells by culture of undigested pulp pieces; (3) digestion of pulp tissue pieces and fixing them. The cells were cultured in minimum essential medium alpha modification (αMEM) medium supplemented with 20% fetal bovine serum(FBS) in humid 37°C incubator with 5% CO 2 . The markers of stem cells were studied by reverse transcriptase polymerase chain reaction (PCR). The student t-test was used for comparing the means of independent groups. P <0.05 was considered as significant. Results: The results indicated that by the first method a few cell colonies with homogenous morphology were detectable after 4 days, while in the outgrowth method more time was needed (10-12 days) to allow sufficient numbers of heterogeneous phenotype stem cells to migrate out of tissue. Interestingly, with the improved third method, we obtained stem cells successfully with about 60% efficiency after 2 days. The results of RT-PCR suggested the expression of Nanog, Oct-4, and Nucleostemin markers in the isolated cells from dental pulps. Conclusion: This study proposes a new method with high efficacy to obtain dental pulp stem cells in a short time.